GE_GERICHTE P/8189/2015 vom 24. August 2016 - GE Cour de justice (2016)
VOIES DE FAIT; IN DUBIO PRO REO ; EXEMPTION DE PEINE; INDEMNITÉ(EN GÉNÉRAL); TORT MORAL; DÉFENSE DE CHOIX | CP126; CP177.3; CP47; CPP429.1.c; CPP433.1